2020
DOI: 10.1093/milmed/usz277
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Army Combat Medic eFAST Performance with a Novel Versus Conventional Transducers: A Randomized, Crossover Trial

Abstract: Background Point-of-injury extended focused assessment with sonography in trauma (eFAST) may identify life-threatening torso hemorrhage and expedite casualty evacuation. The purpose of this study was to compare combat medic eFAST performance between the novel and conventional ultrasound (US) transducers. Methods We conducted a randomized crossover trial. Medic participants, previously naïve to US, were randomized to the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…24 Previous research has shown emergency medical technicians can be trained in trauma sonography after a brief training intervention to achieve results comparable to physicians. [25][26][27] Participants performed all FASTs on an US phantom model, not a live human model or an actual trauma patient. This limits generalizability as patient factors such as obesity, difficult sonographic windows, movement, pain, altered mentation, and several others may complicate FAST performance.…”
Section: Limitationsmentioning
confidence: 99%
“…24 Previous research has shown emergency medical technicians can be trained in trauma sonography after a brief training intervention to achieve results comparable to physicians. [25][26][27] Participants performed all FASTs on an US phantom model, not a live human model or an actual trauma patient. This limits generalizability as patient factors such as obesity, difficult sonographic windows, movement, pain, altered mentation, and several others may complicate FAST performance.…”
Section: Limitationsmentioning
confidence: 99%